Structural Investigations of the Inhibition of Escherichia coli AmpC β-Lactamase by Diazabicyclooctanes - Lang, Pauline A. (Antimicrob Agents Chemother, 2021)
β-Lactam antibiotics are presently the most important treatments for infections by pathogenic Escherichia coli, but their use is increasingly compromised by β-lactamases, including the chromosomally encoded class C AmpC serine-β-lactamases (SBLs). The diazabicyclooctane (DBO) avibactam is a potent AmpC inhibitor; the clinical success of avibactam combined with ceftazidime has stimulated efforts to optimize the DBO core. We report kinetic and structural studies, including four high-resolution crystal structures, concerning inhibition of the AmpC serine-β-lactamase from E. coli (AmpC(EC)) by clinically relevant DBO-based inhibitors: avibactam, relebactam, nacubactam, and zidebactam. Kinetic analyses and mass spectrometry-based assays were used to study their mechanisms of AmpC(EC) inhibition. The results reveal that, under our assay conditions, zidebactam manifests increased potency (apparent inhibition constant [K(iapp)], 0.69 μM) against AmpC(EC) compared to that of the other DBOs (K(iapp) = 5.0 to 7.4 μM) due to an ∼10-fold accelerated carbamoylation rate. However, zidebactam also has an accelerated off-rate, and with sufficient preincubation time, all the DBOs manifest similar potencies. Crystallographic analyses indicate a greater conformational freedom of the AmpC(EC)-zidebactam carbamoyl complex compared to those for the other DBOs. The results suggest the carbamoyl complex lifetime should be a consideration in development of DBO-based SBL inhibitors for the clinically important class C SBLs.